Strategies for 14C Dating the Oxtotitlán Cave Paintings, Guerrero, Mexico. Issue 2 (27th March 2017) - Russ, Jon; Pohl, Mary D.; von Nagy, Christopher L.; Steelman, Karen L.; Hurst, Heather; Ashby, Leonard; Schmidt, Paul; Padilla Gutiérrez, Eliseo F.; Rowe, Marvin W.
ABSTRACT: Oxtotitlán Cave paintings have been considered among the earliest in Mesoamerica on stylistic grounds, but confirmation of this hypothesis through absolute dating has not been attempted until now. We describe the application of advanced radiocarbon strategies developed for situations such as caves with high carbon backgrounds. Using a low-temperature plasma oxidation system, we dated both the ancient paint and the biogenic rock coatings that cover the paint layers at Oxtotitlán. Our research has significantly expanded the time frame for the production of polychrome rock paintings encompassing the Early Formative and Late Formative/Early Classic periods, statistically spanning a long era from before ca. 1500 cal B.C. to cal A.D. 600. Abstract : Los murales de la Cueva de Oxtotitlán, de acuerdo con criterios estilísticos, han sido considerados entre los más tempranos de Mesoamérica. Sin embargo, hasta la fecha esta hipótesis no había sido corroborada mediante fechamiento absoluto. En este trabajo se describe la aplicación de técnicas de radiocarbono avanzadas, las cuales han sido desarrolladas para lugares como cuevas con un elevado fondo de carbón. Fechamos tanto la pintura antigua como los recubrimientos biogénicos que cubren las capas de pintura utilizando un sistema de oxidación de plasma a temperatura baja. Nuestras investigaciones han ampliado de manera significativa el intervalo temporal de la pintura mural policroma en Mesoamérica, abarcando los periodos del Formativo Temprano al Formativo Tardío/Clásico Temprano, desde antes de aproximadamente 1500 cal a.C. hasta 600 cal d.C.